2013
DOI: 10.1371/journal.pone.0061796
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension Is Not Associated with All-Cause Mortality: A Systematic Review and Meta-Analysis of Prospective Studies

Abstract: ObjectivesQuantitative associations between prehypertension or its two separate blood pressure (BP) ranges and cardiovascular disease (CVD) or all-cause mortality have not been reliably documented. In this study, we performed a comprehensive systematic review and meta-analysis to assess these relationships from prospective cohort studies.MethodsWe conducted a comprehensive search of PubMed (1966-June 2012) and the Cochrane Library (1988-June 2012) without language restrictions. This was supplemented by review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 46 publications
3
13
0
3
Order By: Relevance
“…Determining this association is important in clarifying prefrailty as an important diagnostic entity in itself versus another early disease state. Although some preconditions such as prehypertension have been well defined, no association has been found between prehypertension and overall mortality . This is unlike other precondition states such as prediabetes, for which a metaanalysis demonstrated an associated greater risk of all‐cause and cardiovascular mortality when defined according to fasting glucose as low as 5.6 mmol/L .…”
Section: Discussionmentioning
confidence: 96%
“…Determining this association is important in clarifying prefrailty as an important diagnostic entity in itself versus another early disease state. Although some preconditions such as prehypertension have been well defined, no association has been found between prehypertension and overall mortality . This is unlike other precondition states such as prediabetes, for which a metaanalysis demonstrated an associated greater risk of all‐cause and cardiovascular mortality when defined according to fasting glucose as low as 5.6 mmol/L .…”
Section: Discussionmentioning
confidence: 96%
“…7 Meta-analyses of observational prospective studies suggested that people with SBP 120 to 139 mm Hg and/or DBP 80 to 89 mm Hg may also be at risk of cardiovascular events. [8][9][10][11][12][13][14][15][16][17] For this group of people, it was observed that the higher the BP was, the higher the cardiovascular risk was, in general. However, the risk was less significant and less clearly established in Asians, except for the risk of stroke which was shown to be lower, similar to, or even higher than that for non-Asians from different metaanalyses.…”
Section: Benefits Of a Lower Blood Pressure Definition And Treatment mentioning
confidence: 83%
“…A pré-hipertensão, como a própria denominação sugere, ocorre anteriormente à hipertensão e está associada com um risco aumentado de doenças cardiovasculares, principalmente para aqueles indivíduos classificados como pré-hipertensos em uma faixa mais elevada, chamada high-range prehypertension 25,26 , na qual a pressão arterial sistólica está entre 130 e 139 mmHg e a diastólica, entre 85 e 89 mmHg, o equivalente à pressão normal alta ou limítrofe da classificação brasileira 1 . Os desfechos fatais devido a doenças cardiovasculares aumentam de forma linear e contínua a partir de PAS 115 mmHg e de PAD 75 mmHg 1,13,25,26 .…”
Section: Discussionunclassified
“…Como recomendação primária, tem-se a abordagem não medicamentosa, que inclui mudanças no estilo de vida e a adoção de hábitos mais saudáveis, como a diminuição do consumo de álcool e da ingestão de sódio, a incorporação de atividades físicas e a eliminação do fumo 1 . Por outro lado, algumas pesquisas têm demonstrado eficácia suficiente e segura do tratamento anti-hipertensivo para pré-hipertensão, porém ainda não foi comprovado se os benefícios da terapia farmacológica superam os malefícios e não existem ainda evidências que justifiquem tal procedimento 25,27 .…”
Section: Discussionunclassified